2012
DOI: 10.1111/ctr.12047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recipient age on whole organ pancreas transplantation

Abstract: No statistically significant differences in pancreas transplant outcomes were demonstrated when recipients were stratified by recipient age. These results suggest that older recipients can successfully undergo pancreas transplantation and expect five-yr outcomes similar to those seen in younger recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…In 2013, Shah et al . published their experience with 405 pancreas transplants. Patients were stratified by age; among these, 85 patients were aged 50–59 years and 18 patients were 60 years or older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Shah et al . published their experience with 405 pancreas transplants. Patients were stratified by age; among these, 85 patients were aged 50–59 years and 18 patients were 60 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…However, this exclusionary practice has been based on limited data. Some authors have described acceptable outcomes in older patients, whereas others have remained more cautious . However, the risk versus benefit ratio for procedures such as pancreas transplantation can change dramatically over time as outcomes improve and as risk factors, both modifiable and nonmodifiable, become better appreciated .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ojo in 2001 showed no survival benefit for simultaneous pancreas kidney transplantation (SPK) recipients over age 50; however, this study only had 38 patients over 50 . In 2011, Shah showed no difference in graft or patient survival when comparing patients over the age of 50 (n = 103) with younger pancreas transplant recipients (n = 302) . Our study of the UNOS database demonstrated a statistically significant difference in patient and graft survival when comparing different age groups.…”
Section: Discussionmentioning
confidence: 62%
“…This is not the first study on the subject of pancreas transplantation in the elderly; hence, the result is even less surprising. Besides some retrospective single‐centre analyses that came to similar conclusions, a UNOS database review of 20 854 patients exists and includes 3160 patients between 50 and 59 years and 280 over 60‐year old at the time of transplantation . In this register‐based analysis, an increasing patient age correlated with a significant decrease in patient and graft survival, especially in the group aged over 60 years.…”
mentioning
confidence: 91%